Instalaciones fílmicas: Entre la “muerte del cine” y la resistencia en el arte contemporáneo - Gallegos, Fabiana (2019)
Film installations are an art practice that locates the –already obsolete cinematic apparatus in a contemporary art space, outside of the traditional cinema theater or black cube. Various artists coming from visual and audiovisual arts have begun to create fi lm installations that, far from considering it obsolete, propose a redefi nition of cinema and a resistance against the so called “death of cinema”, through an aesthetic and epistemological expansion of the cinematic apparatus.Even though these works haven’t awoke particular interest in being studied because of their specifi city within the vast and diverse territory of audiovisual installation, it is necessary to pay attention to this kind of hybrid and anachronistic proposals between fi lm and visual arts, especially in a context in which it is possible to detect an immanent proliferation of the moving image in museums, and the digital image imposes itself as the primary format in the cinema industry while at the same time an entire system of fi lm as a medium disappears. (Traducido por Natalia Cortesi)